2021
DOI: 10.1038/s41587-020-00778-3
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining high-throughput profiling of reactive cysteines for cell-based screening of large electrophile libraries

Abstract: Current methods used for measuring amino acid side-chain reactivity lack the throughput needed to screen large chemical libraries for interactions across the proteome. Here we redesigned the workflow for activity-based protein profiling of reactive cysteine residues by using a smaller desthiobiotin-based probe, sample multiplexing, reduced protein starting amounts and software to boost data acquisition in real time on the mass spectrometer. Our method, streamlined cysteine activity-based protein profiling (SLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
347
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(363 citation statements)
references
References 71 publications
13
347
1
2
Order By: Relevance
“…The Figure 5. A) Cysteines and B) cysteine proteins identified experimentally in Backus et al, [12] Gygi et al, [58] in the current study, those theoretically detectable based on in silico trypsin digestion, and all found in Uniprot/Swiss-Prot sequences. C) Venn diagram of unique cysteines identified in current study and Gygi et al All data can be found in Table S5.…”
Section: Sp3-faims Chemoproteomic Analysis Of a Panel Of Cell Lines Protease Digests And Subcellular Fractionssupporting
confidence: 58%
See 1 more Smart Citation
“…The Figure 5. A) Cysteines and B) cysteine proteins identified experimentally in Backus et al, [12] Gygi et al, [58] in the current study, those theoretically detectable based on in silico trypsin digestion, and all found in Uniprot/Swiss-Prot sequences. C) Venn diagram of unique cysteines identified in current study and Gygi et al All data can be found in Table S5.…”
Section: Sp3-faims Chemoproteomic Analysis Of a Panel Of Cell Lines Protease Digests And Subcellular Fractionssupporting
confidence: 58%
“…For comparison, our prior study identified only 15.0 and 14.6 % of proteins, respectively (Figure 5B). As Gygi et al recently reported a new high throughput and high coverage cysteine chemoproteomic method, streamlined cysteine activity-based protein profiling (SLC-ABPP), [58] we additionally opted to benchmark our dataset against their comprehensive inventory of chemoproteomic-detected cysteines. We find that the SP3-FAIMS method identified~31 % more cysteines and~18 % more proteins, using only a fraction of the instrument time (Figure 5).…”
Section: Sp3-faims Chemoproteomic Analysis Of a Panel Of Cell Lines Protease Digests And Subcellular Fractionsmentioning
confidence: 99%
“…In recent years the scope, scale, and speed with which chemically reactive amino acids can be profiled has accelerated dramatically; chemoselective probes are now available for cysteine 4 , serine 39 , lysine 5 , methionine 6 , tyrosine 7 , aspartate/glutamate 9,40 , tryptophan 41 , and histidine 42 . Supporting this, advances in mass-spectrometry have significantly expanded the number and rate at which individual reactive sites can be profiled 43,44 , and subsequently exploited by electrophilic drug hunters. CORe provides a technology bridge between unbiased proteomic profiling of reactive sites and protein sequence-function relationships, and will be a valuable tool for proteome engineers alongside other methods including MAGE, CRMAGE and CREATE.…”
Section: Discussionmentioning
confidence: 99%
“…Several variants of the latter have been published (e.g. [91,92],) which differ in aspects including the exact probe design with either preinstalled or latent affinity handle as well as quantitative MS strategy with the final sample consisting of enriched probelabeled peptides. Signal reduction for a specific probemodified peptide upon cell pre-treatment with a compound of interest is used to infer compound labeling of a target residue.…”
Section: Affinity-enrichmentbased Chemoproteomic Approachesmentioning
confidence: 99%
“…In this case, the covalent library members do not need additional features to be compatible with the workflow (compared to the PAL equivalent mentioned previously), so that throughput becomes a key limiting factor for screening applications. This has led to the recent report of a scaled-down TMTbased streamlined cysteine (SLC)-ABPP workflow [91] which allows profiling of 8,000 cysteine residues in 18 minutes per compound with reduced input material requirements. While these workflows are used so far predominantly for cysteinetargeting compounds, they can per se be applied to any reactive amino acids for which pan-reactive probes are available.…”
Section: Affinity-enrichmentbased Chemoproteomic Approachesmentioning
confidence: 99%